THE CORRELATION BETWEEN VOCABULARY LEARNING STRATEGIES AND VOCABULARY KNOWLEDGE OF ENGLISH-SPECIALIZED STUDENTS AT LE HONG PHONG GIFTED HIGH SCHOOL = MỐI TƯƠNG QUAN GIỮA PHƯƠNG PHÁP HỌC TỪ VỰNG VÀ KIẾN THỨC TỪ VỰNG CỦA HỌC SINH CHUYÊN ANH TRƯỜNG THPT CHUYÊN LÊ HỒNG PHONG - Trần, Thị Bảo Ngọc (2020)
This study was conducted in an attempt to explore the correlation between direct and indirect vocabulary learning strategies with the depth and breadth of vocabulary knowledge of English-specialized students at Le Hong Phong Gifted High School in Nam Dinh City. A total of 186 students completed a questionnaire concerning vocabulary learning strategy use. Subsequently, Vocabulary Levels Test (Schmitt et al., 2001) and Word Associates Test (Read, 1993; Read, 2004) were administered to measure the breadth and depth of lexical repertoire respectively. The results indicated that direct strategies were more frequently used by the students. Moreover, it was found that participants’ scores in strategy use correlated significantly and positively with breadth and depth of vocabulary knowledge. Indirect strategy use had a quite high correlation with two dimensions of vocabulary knowledge, implying that the students that had a large vocabulary size and a deep understanding of lexical repertoire tended to combine both direct and indirect strategies instead of using only one kind. Also, this highlights the importance of direct and indirect cognitive strategies, e.g., self-planning, self-monitoring, and self-evaluating. Relevant pedagogical implications were also discussed in the last chapter of this paper.